Biomedical Applications: Gram‐Negative Bacteria Targeting Mediated by Carbohydrate–Carbohydrate Interactions Induced by Surface‐Modified Nanoparticles (Adv. Funct. Mater. 48/2019). (26th November 2019) - Capeletti, Larissa Brentano; de Oliveira, Jessica Fernanda Affonso; Loiola, Lívia Mesquita Dias; Galdino, Flávia Elisa; da Silva Santos, Denys Ewerton; Soares, Thereza Amélia; de Oliveira Freitas, Raul; Cardoso, Mateus Borba
Abstract : In article number 1904216, Mateus Borba Cardoso and co‐workers demonstrate that nanoparticles fuctionalized with gluconamide moieties present selective targeting ability to Gram‐negative bacteria membranes and no significant toxicity to mammalian or red blood cells. In addition, gluconamide functionality also provides tunable antibiotic delivery abilities, high stability in complex biological media, and lack of non‐specific protein adhesion.